O curso de licenciatura em educação física do ICSEZ/UFAM: aspectos facilitadores e desafiadores na visão dos acadêmicos - Barroso, Izaias dos Santos (Brasil, 2023)
The research aims to understand the factors that hinder/facilitate students' retention in the undergraduate Physical Education program at ICSEZ/UFAM. A qualitative-quantitative field study was conducted, with a sample consisting of 78 students enrolled in the Physical Education program at ICSEZ-UFAM. Data were collected through a questionnaire to assess students' profiles and identify the factors that hinder/facilitate their retention in the program. The data revealed that over 80% of the interviewed students had considered dropping out of the program. Financial, emotional, and social difficulties, such as lack of transportation, financial insufficiency, lack of time for extracurricular activities, and distance from family, were identified as factors affecting students' retention. On the other hand, aspects that facilitate students' retention in the program include the prospect of good employment, student assistance, and involvement in extracurricular activities. It was found that students' effective retention and their sense of belonging to the university community are directly linked to the relationships they establish in the academic environment. The quality of these relationships, social support, feelings of inclusion and recognition, as well as opportunities for active participation in university life, directly influence students' academic journey and continuation of their studies. It is concluded that the indicated results provide enlightening information for the institution to reconsider or strengthen its strategies, with a focus on student retention and persistence.